2017
DOI: 10.1111/petr.12904
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral transplantation for abdominal tumors in children: A single center experience and review of the literature

Abstract: Standard management of intra-abdominal pediatric solid tumors requires complete resection. However, tumors with multiple organ and vascular involvement present a unique surgical challenge. We conducted a retrospective chart review of four patients, aged 2-14 years, undergoing MVT for intra-abdominal tumors with significant involvement of the visceral arteries and/or portomesenteric venous system at our institution. Indications for MVT included hepatocellular carcinoma, inflammatory myofibroblastic tumor, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Invasive desmoid tumors in those with Gardner syndrome have been listed in reports for indications of multivisceral transplant 22 . In addition, neuroendocrine tumors with liver metastases or primary hepatic tumors invading the mesenteric vessels have been described with good results after multivisceral transplant 54,55 . Thus, consideration should be given to any tumor where complete resection must be performed and such resection would involve the liver and abdominal viscera.…”
Section: Other Indicationsmentioning
confidence: 99%
“…Invasive desmoid tumors in those with Gardner syndrome have been listed in reports for indications of multivisceral transplant 22 . In addition, neuroendocrine tumors with liver metastases or primary hepatic tumors invading the mesenteric vessels have been described with good results after multivisceral transplant 54,55 . Thus, consideration should be given to any tumor where complete resection must be performed and such resection would involve the liver and abdominal viscera.…”
Section: Other Indicationsmentioning
confidence: 99%
“…In a larger series of 27 patients with POST-TEXT III or IV who underwent extended liver resections with or without resection of adjacent structures, 5-year OS was 81% while 5-year EFS was 62% [ 37 ]. Several cases of successful multivisceral transplant (MVT) for hepatoblastoma extending into the portomesenteric vessels have been described as well [ 39 , 40 ]. In the series of Lee et al two patients with hepatoblastoma undergoing MVT are described; after 4.5 and 8 years of follow up respectively there was no evidence of tumour recurrence.…”
Section: Extreme Liver Resections and With Resection Of Adjacent Orga...mentioning
confidence: 99%
“… 60 , 61 , 62 Even more surprising is that multi‐visceral transplantation achieved complete gross resection of extensive HB with multiple organ and vascular involvement, providing long‐term disease‐free survival (4.5 and 7.8 years) in pediatric patients with no other surgical options. 63 On the basis of a multi‐center retrospective analysis, Pondrom et al indicated that tumor rupture might be predictive of poor prognosis with a risk of peritoneal relapse, but it should not be a contraindication for LT. 64 In 2004, an era in which chemotherapy regimens and surgical skills for HB were developing, Otte et al reported an overall survival rate of only 30% for 41 HB patients who underwent a salvage LT. 5 However, the latest Japanese multi‐center study showed that there was no significant difference in the 1‐ and 5‐year survival rates between HB patients undergoing primary LT and those who received salvage LT for tumor recurrence (89.7%, 81.6% vs. 88.0%, 76%; p = 0.526). 65 These data are similar to the latest SPLIT results showing 85% and 74% salvage transplant event‐free survival rates at 1 and 3‐years, respectively.…”
Section: Current Status Of Lt and The Application ...mentioning
confidence: 99%
“…When major vessels were invaded by the tumor, vein graft replacement or portal venous tumor thrombectomy was applied successfully 60–62 . Even more surprising is that multi‐visceral transplantation achieved complete gross resection of extensive HB with multiple organ and vascular involvement, providing long‐term disease‐free survival (4.5 and 7.8 years) in pediatric patients with no other surgical options 63 . On the basis of a multi‐center retrospective analysis, Pondrom et al indicated that tumor rupture might be predictive of poor prognosis with a risk of peritoneal relapse, but it should not be a contraindication for LT 64 .…”
Section: Current Status Of Lt and The Application Of Transplant Techn...mentioning
confidence: 99%